An empirical analysis of human trafficking in an era of globalization - Yselle F. Malah; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
The paper explores the dark side of economic openness by examining empirically the nexus between the globalization process and human trafficking. Specifically, it is about showing in a global perspective how the growing process of free movement of people, goods, capital, services and information technology make the globe a connected web of activity for the sale and exploitation of human beings. After discussing some transmission channels through which globalization could increase this practice based on the lessons from the literature, an empirical analysis is done by employing OLS and Probit regressions on a cross-sectional model covering 130 countries worldwide. Findings, robust to the consideration of the subregional specificities and controlling for social, cultural and historical factors, suggest that globalization, particularly financial and cultural, favors human trafficking. In the light of these results, some policy recommendations are discussed.
Keywords: F53; C21; 330; globalization; human trafficking; cross section model